Dissolved Gas Analysis: A Proactive Approach for Recognization of Faults in Transformer using MATLAB GUI - Babukutty, Simon; Khule, S.S. (Journal of Advanced Research in Signal Processing and Applications, 2021)
Transformer plays an important role in Power transmission network. For a reliable power supply utmost attention is required. The mineral oil employed is exposed to high thermal and electrical stresses and thus gasses are formed due putrefaction of the mineral oil. To reduce the failure in transformers diagnosis of mineral oil for faults needs to be carried out. The Dissolved gas analysis (DGA) is used for assessment of oil for liquified gases formed due to faults. DGA involves five classical methods Key Gas Method, IEC Ratio method, Rogers Ratio Method, Doernenburg Ratio Method and Duval triangle Method. This paper presents a MATLAB GUI for five classical methods with 93% accuracy when compared to reliable individual method of 83% accuracy.               How to cite this article: Babukutty S, Khule SS. Dissolved Gas Analysis: A Proactive Approach for Recognization of Faults in Transformer using MATLAB GUI. J Adv Res Sig Proc Appl 2019; 1(2): 23-28.